Analysis of Local Knowledge of Community in Protecting the Environment: Case Study Kampung Salo Sub-district, Kendari City - Saputra, Randi Adrian; Arial, Jimy Dwi; Sakti, Sari Fadilah; Mariani; Zebua, Petrus Somaogo; Khairiyah, Shofa' Nur Amirah (Journal of Geographical Sciences and Education, 2024)
Environmental damage is a problem that is always faced in urban areas including Kendari city, including the physical, social, and biological environment. Areas with crowded settlements are always a concern for the level of environmental damage. This research aims to determine the local knowledge of the community of Kampung Salo in protecting the environment. This type of research is qualitative research using interactive analysis. The data analysis technique uses interactive analysis which consists of four stages of the analysis model, namely data collection, data reduction, data presentation, and conclusion. The research results show that only 21.9% of the community of Kampung Salo understands the importance of protecting the environment. The main factor in the lack of understanding of the Kampung Salo community in protecting the environment is the lack of education and lack of public awareness. Thus, intensive action from the government is necessary to help sensitize the community in protecting the environment.